Creditors - Veress , Emőd (Joint Stock and Limited Liability Companies in East Central Europe, 2025)
References: Barbić, J. (2010) Pravo društava: Društva kapitala, Svezak I. i II. Zagreb: Organizator. Bezzenberger, T. (2005) Das Kapital der Aktiengesellschaft. Köln: Otto Schmidt. Bolesta-Kukuła, K. (2003) Decyzje menedżerskie. Warszawa: Polskie Wydawnictwo Ekonomiczne (PWE). Cărpenaru, St.D. (2019) Tratat de drept comercial roman, 6th edn. București: Universul Juridic. Černá, S., Štenglová, I., Pelikánová, I. et al. (2021) Pravo obchodnich korporaci, 2nd edn. Praha: Wolters Kluwer. Charkiewicz, M., Chilimoniuk, M. (2022) ‘Economic aspects of business bankruptcy’, Zeszyty Naukowe. Seria: Zarządzanie i Finanse, 26(2), pp. 9–20. Csach, K. (2019) ‘Povinnosti členov orgánov obchodnej spoločnosti a súkromnoprávne následky ich porušenia (2. časť)’, Sukromne pravo, 5(6), pp. 222–232. Dolný, J. (2021) Odporovateľnosť pravnych ukonov v konkurznom prave. Bratislava: C.H. Beck. Ďurica, M. (2019) Zakon o konkurze a reštrukturalizacii. Komentar, 3rd edn. Praha: C.H. Beck. Goette, K., Fleischer, H. (eds.) (2018) Munchener Kommentar zum GmbH-Gesetz, Band 1 (§§ 1–34), 3rd edn. München: C.H. Beck. Gurgul, S. (2010) ‘Odpowiedzialność wspólnika (akcjonariusza) za zobowiązania spółki kapitałowej w stosunku do jej wierzycieli’, Monitor Prawniczy, 2010/20, pp. 1146–1151. High Level Group of Company Law Experts (2002) Report of the High Level Group of Company Law Experts on a Modern Regulatory Framework for Company Law in Europe. Brussels: European Commission. Höfer, C. (2016) “Flex-GmbH ” – eine solvenzorientierte Schwester-Rechtsform für die GmbH?’, Zeitschrift fur Gesellschaft-, Unternehmens- und Steuerrecht der GmbH und GmbH & Co. KG, (8), pp. 398–405. Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba. Ivkošić, M. (2020) ‘Kapitalno orijentirani sustav zaštite vjerovnika društva s ograničenom odgovornošću’, Zbornik Pravnog fakulteta u Zagrebu, 70(1), pp. 107–135 [Online]. Available at: https://hrcak.srce.hr/238492 (Accessed: 10 October 2025). Jevremović-Petrović, T. (2011) ‘Poverioci u kompanijskom pravu i instrumenti njihove zaštite’, Anali Pravnog fakulteta u Beogradu, 59(1), pp. 223–254. Jevremović-Petrović, T. (2012) ‘Directors’ responsibility to creditors in Company Law’, Anali Pravnog fakulteta u Beogradu, 60(3), pp. 149–169 [Online]. Available at: https://doi.org/10.2139/ssrn.4246915 (Accessed: 10 October 2025). Jurić, D. (2019) Pravo društava. Rijeka: Pravni fakultet Sveučilišta u Rijeci. Keay, A. (2007) Company Directors’ Responsibilities to Creditors, 1st edn. London: Routledge. Lasák, J., Dědič, J., Pokorná, J., Čáp, Z. et al. (2021) Zakon o obchodnich korporacich. Komentař, 2nd edn. Praha: Wolters Kluwer ČR. Lieder, J. (ed.) (2018) European Corporate Law: Article-by-Article Commentary. Baden- Baden: Nomos / München: C.H. Beck / Oxford: Hart. Lokajíček, J. (2016) Prolomeni majetkove samostatnosti kapitalovych společnosti. Praha: C. H. Beck. Lutter, M., Hommelhoff, P. (2023) GmbH-Gesetz Kommentar, 21st edn. Köln: Otto Schmidt. Marjanski, V., Dudás, A. (2020) ‘Some Current Problems with the Regulation of Limited Liability Companies in Serbia’, Central European Journal of Comparative Law, 1(1), pp. 131–145. Merkt, H. (2004) ‘Creditor protection and capital maintenance from a German perspective’, European Business Law Review, 15(6), pp. 1409–1428 [Online]. Available at: https://kluwerlawonline.com/journalIssue/European+Business+Law+Review/15.5/1518 (Accessed: 10 October 2025). Mihajlović, B. (2019) ‘Posebne dužnosti u periodu rizika od stečaja’, Anali Pravnog fakulteta u Beogradu, 67(3), pp. 196–228 [Online]. Available at: https://doi.org/10.5937/AnaliPFB1903196M (Accessed: 10 October 2025). Mohai, M. (2022) ‘Tagi felelősségátvitel a társaságok jogában’, Gazdasag es Jog, 2022/5–6, pp. 21–28. Moţu, F.I. (2015) Acțiunea in anularea actelor frauduloase. București: Universul Juridic. Mrázová, Ž., Husár, J., Dolný, J. et al. (2021) Volene organy kapitalovych spoločnosti. Vybrane otazky. Košice: ŠafárikPress. Osajda, K. (2017) ‘Ochrona wierzycieli spółek kapitałowych w orzecznictwie Sądu Najwyższego’, Przegląd Prawa Handlowego, 2017/9, pp. 8–19. Ovečková, O. et al. (2022) Obchodny zakonnik. Veľky komentar, vol. I, 2nd edn. Bratislava: Wolters Kluwer SR. Ovečková, O., Csach, K., Žitňanská, L. (2020) Obchodne pravo: obchodne spoločnosti a družstvo. Bratislava: Wolters Kluwer SR. Patakyová, M., Ďurica, M., Husár, J. et al. (2021) Aplikovane pravo obchodnych spoločnosti a družstva – ťažiskove inštituty. Bratislava: Wolters Kluwer SR. Pawluczuk-Bućko, P. (2022) ‘„Taktyczna upadłość” – rozważania na tle art. 301 k.k.’, Prokuratura i Prawo, 2022/9, pp. 69–100. Petrović, S., Ceronja, P. (2019) Osnove prava društava. Zagreb: Narodne novine. Piperea, Gh. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S. Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck, pp. 198–224. Pokorná, J., Lasák, J., Kotásek, J. et al. (2022) Obchodni společnosti a družstva, 2nd edn. Praha: C. H. Beck. Przybyła, A., Kucinoglu, K. (2023) ‘Business Judgment Rule. Miernik biznesowej oceny działań członków organów spółek kapitałowych’, Edukacja Prawnicza, 182(1), pp. 62–65. Radović, V. (2009) ‘Značajan gubitak i obaveza sazivanja sednice skupštine’, Pravni život, 58(12), pp. 307–322. Radović, V. (2020) Osnovi stečajnog prava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Richter, T. (2017) Insolvenčni pravo. Praha: Wolters Kluwer. Roth, G.H., Kindler, P. (2013) The Spirit of Corporate Law: Core Principles of Corporate Law in Continental Europe. Baden-Baden, Oxford, and Munich: Nomos, Hart, C.H. Beck. Schmidt, K. (2004) ‘Verbotene Zahlungen in der Krise von Handlungsgesellschaften und die daraus resultierenden Ersatzpflichten’, Zeitschrift fur das gesamte Handelsrecht und Wirtschaftsrecht (ZHR), 168(3), pp. 401–432. Sprinz, P., Jirmásek, T., Řeháček, O., Vrba, M., Zoubek, H. et al. (2023) Insolvenčni zakon. 1st edn (4th update). Praha: C. H. Beck. Štenglová, I., Dědič, J., Lasák, J., Pihera, V., Lála, D., Josková, L. (2023) Akciove společnosti, 1st edn. Praha: C. H. Beck. Strzelczyk, K. (2001) in Naworski, J.P., Strzelczyk, K., Siemiątkowski, T., Potrzeszcz, R. Komentarz do Kodeksu społek handlowych. Społka z ograniczoną odpowiedzialnością. Warszawa: Wydawnictwo Prawnicze LexisNexis. Szumański, A. (2005) Kodeks społek handlowych. Komentarz. Tom II: komentarz do artykułow 151–300. Warszawa: C.H. Beck. Tomczak, S.K. (2018) ‘Statistics on bankruptcy of companies in Poland’, Nauki o Zarządzaniu = Management Sciences, 23(3), pp. 39–50 [Online]. Available at: https://doi.org/10.15611/ms.2018.3.05 (Accessed: 10 October 2025). Turcu, I. (2015) Codul insolvenței: Legea nr. 85/2014, 5th edn. București: C.H. Beck. Vasiljević, M., Jevremović-Petrović, T., Lepetić, J. (2020) Kompanijsko pravo – pravo privrednih društava, 1st edn. Beograd: Službeni glasnik RS. Veress, E. (2024a) ‘Állandó és változó elemek a kft. szabályozásában. 1. rész – A “korlátolt felelősség”’, Gazdasag es Jog, 2024/7–8, pp. 3–9. Veress, E. (2024b) ‘A nehézségekkel küzdő vállalat’ in Fegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris. Vuković, A. and Bodul, D. (2012) ‘Stečajno zakonodavstvo u tranziciji – komparativni osvrt, hrvatski izazovi i potencijalna rješenja’, Zbornik radova Pravnog fakulteta u Splitu, 49(3), pp. 633–661 [Online]. Available at: https://hrcak.srce.hr/file/129226 (Accessed: 10 October 2025). Zabel, B. (2006) ‘8. člen: spregled pravne osebnosti’ in Kocbek, M. (ed.) Veliki komentar Zakona o gospodarskih družbah, 1st edn. Ljubljana: GV Založba, pp. 157–167.